2002
DOI: 10.1086/341607
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Locus for Adolescent Idiopathic Scoliosis Linked to Chromosome 19p13.3

Abstract: Adolescent idiopathic scoliosis (AIS) is one of the most common orthopedic disorders, affecting up to 4% of schoolchildren worldwide. We studied seven unrelated multiplex families of southern Chinese descent with AIS, consisting of 25 affected members. A genomewide scan with >400 fluorescent microsatellite markers was performed. Multipoint linkage analysis by GENEHUNTER revealed significant linkage of the abnormal phenotype to the distal short arm of chromosome 19, with both a maximum multipoint LOD score and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
100
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 14 publications
3
100
1
3
Order By: Relevance
“…A genome-wide scan of seven unrelated multiplex families of Chinese descent with AIS concluded that there was a linkage to chromosome 19p13.3 (IS1, MIM 181800). 8 This finding was replicated in several IS multiplex families in Alden et al's study. 9 A similar study in an Italian family mapped a second locus to 17p11.2 (IS2, MIM 607354).…”
Section: Introductionmentioning
confidence: 66%
“…A genome-wide scan of seven unrelated multiplex families of Chinese descent with AIS concluded that there was a linkage to chromosome 19p13.3 (IS1, MIM 181800). 8 This finding was replicated in several IS multiplex families in Alden et al's study. 9 A similar study in an Italian family mapped a second locus to 17p11.2 (IS2, MIM 607354).…”
Section: Introductionmentioning
confidence: 66%
“…Although familial predisposition to scoliosis points unequivocally to genetic background of this condition, the exact mechanism of inheritance still has to be confirmed. The AIS-associated loci were identified on both autosomes [16][17][18] and the X chromosome [19]. Therefore, a polygenic inheritance model with incomplete penetrance and variable expression (DNA methylation) is postulated [3,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…5 Inoue et al 6 reported AIS concordance rates as 92.3% in monozygotic twins, and 62.5% in dizygotic twins. Recent genome-wide linkage analyses have identified many predisposing loci of AIS, [7][8][9][10][11][12][13][14][15][16] further supporting a role of genetic factor(s) in AIS. Single nucleotide polymorphisms (SNPs) in the genes for estrogen receptor 1 (ESR1), 17 estrogen receptor 2 (ESR2), 18 matrilin 1 (MATN1), 19 melatonin receptor 1B (MTNR1B), 20 and tryptophan hydroxylase 1 (TPH1) 21 are reported to be associated with AIS predisposition.…”
mentioning
confidence: 99%